Consensus of Teleoperating Cyber-Physical System via Centralized and Decentralized Controllers - Yan, Jing; Yang, Xian; Luo, Xiaoyuan; Chen, Cailian; Guan, Xinping (IEEE access, 2017)
Teleoperating cyber-physical system (TCPS) has been considered as a promising technology to stretch artificial intelligences to remote locations. Many applications of TCPS demand operator and slaves to keep state consensus on the shared information. However, the cyberand physicalconstrained characteristics on TCPS make it difficult to realize such a consensus. This paper investigates the consensus problem for single-master-multi-slave TCPS with time-varying delay and actuator saturation. According to the communication structures of slaves, centralized and decentralized controllers are, respectively, designed to drive the consensus of master and slave robots. To simplify the information fusion in decentralized controller design, we use min-weighted rigid graph-based topology optimization algorithm to reduce the communication redundancy in slave site. Under time-varying delay and actuator saturation constraints, the sufficient stability conditions are presented to show that the centralized and decentralized controllers can stabilize the single-master-multi-slave TCPS. Moreover, the stability conditions are rearranged into a form of linear matrix inequalities, and then, the required initial stability conditions for master and slaves are developed. Finally, simulations and experiments are demonstrated to show the validity of the method. It is shown that the consensus controllers can guarantee the asymptotic stability of single-master-multi-slave TCPS, while the topology optimization can reduce the redundancy of communication links.